2009
DOI: 10.1073/pnas.0907813106
|View full text |Cite
|
Sign up to set email alerts
|

Enabling tools for engineering collagenous tissues integrating bioreactors, intravital imaging, and biomechanical modeling

Abstract: Many investigators have engineered diverse connective tissues having good mechanical properties, yet few tools enable a global understanding of the associated formation of collagen fibers, the primary determinant of connective tissue stiffness. Toward this end, we developed a biomechanical model for collagenous tissues grown on polymer scaffolds that accounts for the kinetics of polymer degradation as well as the synthesis and degradation of multiple families of collagen fibers in response to cyclic strains im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 41 publications
(45 reference statements)
3
57
0
Order By: Relevance
“…In the anisotropic case, the y direction indicates the direction of main scaffold fiber orientation. The experimental data are averaged from two samples model is able to predict collagen distributions in agreement with experimental findings (Niklason 2009;de Jonge 2013).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In the anisotropic case, the y direction indicates the direction of main scaffold fiber orientation. The experimental data are averaged from two samples model is able to predict collagen distributions in agreement with experimental findings (Niklason 2009;de Jonge 2013).…”
Section: Discussionsupporting
confidence: 54%
“…6 Fit of the experimental equibiaxial mechanical behavior for the anisotropic scaffold (left). Predicted biaxial mechanical behavior of the isotropic scaffold (right) by using the optimal material parameters of the anisotropic scaffold contact guidance by the scaffold fibers (Niklason 2009;de Jonge 2013), enhanced collagen deposition due to scaffold anisotropy (Lee 2005;Teh et al 2013) or use of cyclic load (Boerboom et al 2008;Rubbens 2009) and load protection from enzymatic degradation (Huang and Yannas 1977;Wyatt et al 2009). It should be noticed that the described phenomena only occur when microfibrous scaffolds are used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An adaptive change in k iv z is consistent with recent findings for native arteries wherein such changes appear to be among the first in many cases of vascular growth or remodeling. 26 Such behavior is understandable since circumferential and axial stiffness, and hence stresses, are coupled tightly, and changes in axial stretch can affect both axial and circumferential mechanics. Most of the earlier reports on native arteries show decreases in axial stretch, however, as an adaptive response to changes in hemodynamic loads.…”
Section: Discussionmentioning
confidence: 99%
“…Heo and colleagues observed that the divergence between the orientation of applied forces and structural anisotropy in a fibrous material alters cellular deformation and differentially influences gene expression (Heo et al, 2011). Given these numerous intricacies, making sense of the effects of exogenous loads on cells embedded within structurally complex materials in 3D will require a combination of experimental and computational modeling approaches (Niklason et al, 2010), thus engendering the need for crossdisciplinary collaborations between biologists and engineers.…”
Section: Mechanotransductionmentioning
confidence: 99%